2020
DOI: 10.1002/btpr.3110
|View full text |Cite
|
Sign up to set email alerts
|

Computational drug repurposing study of the RNA binding domain of SARS‐CoV‐2 nucleocapsid protein with antiviral agents

Abstract: The recent outbreak of coronavirus disease (COVID‐19) in China caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has led to worldwide human infections and deaths. The nucleocapsid (N) protein of coronaviruses (CoVs) is a multifunctional RNA binding protein necessary for viral RNA replication and transcription. Therefore, it is a potential antiviral drug target, serving multiple critical functions during the viral life cycle. This study addresses the potential to repurpose antiviral com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…In a recent study, combination of molecular docking and MD simulation was employed to identify potential antiviral drugs and investigate the stability of the NTD-drug complexes [ 31 ]. 34 antiviral compounds, which were already approved or in development, were focused on because such molecules do not need long-term preclinical studies and thus, they would be excellent candidates in the case of disease outbreaks.…”
Section: Molecular Flexibility and Drug Binding Of N Cov2mentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, combination of molecular docking and MD simulation was employed to identify potential antiviral drugs and investigate the stability of the NTD-drug complexes [ 31 ]. 34 antiviral compounds, which were already approved or in development, were focused on because such molecules do not need long-term preclinical studies and thus, they would be excellent candidates in the case of disease outbreaks.…”
Section: Molecular Flexibility and Drug Binding Of N Cov2mentioning
confidence: 99%
“…Ivermectin, an anti-parasitic drug with antiviral properties, has also been shown to bind to the similar region as the above compounds [ 32 ]. Although each compound also interacts with the residues of the NTD other than those shown in Figure 3 a, none of these residues overlaps with the RNA-binding region except for rapamycin, which shares K65 with the RNA-binding sites [ 31 ]. It is likely that the binding affinity between the NTD and RNA is affected as long as at least one residue is blocked by a drug molecule.…”
Section: Molecular Flexibility and Drug Binding Of N Cov2mentioning
confidence: 99%
See 2 more Smart Citations
“…It makes them into a helical capsid structure or ribonucleoprotein (RNP) complex. Because of this function, it is suggested that the corona virus N protein is an RNA chaperone and performs a main role in viral genomic RNA replication [14,15]. Our present study has been undertaken to compare binding a nity analysis of various natural plants compounds and small molecules against RdRp and Nucleocapsid Proteins of SARS COV 2 by using Molecular Docking Methods [16].…”
Section: Introductionmentioning
confidence: 99%